Product Analysis of the Drinking Water Supply System of PERUMDA Water Drinum Way Rilau Bandar Lampung City Using Segmenting, Targeting, and Positioning Strategies - Dewi, Indah Syakina; Wardianto, Kussuyatmono Bagus (Jurnal Kompetitif Bisnis, 2024)
The Way Rilau Regional Public Company (PERUMDA) drinking water is a BUMD which has a business in the clean water distribution sector, so this company operates in the service and product sector with uniform health standards. One way to initiate make a clean water company is through segmenting, targeting, and positioning. Segmenting, targeting and positioning are methods for analyzing a company’s internal and external strengths so that the company can achieve its goals. This research uses a descriptive qualitative approach with interviews and observations to obtain detailed research results, using primary data sources. The results of the research show that the segmenting carried out by PERUMDA Air Minum Way Rilau for ready-to-drink water products is segmentation based on Geographic, covering 8 areas of the city of Bandar Lampung. Segmentation based on demographics, namely looking at consumers' income, gender, education and age. Segmentation based on psychographics, this company's segmentation looks at the lifestyle of its consumers who always follow developments. Segmentation based on behavior, consumers use more regular water products because this product has been around for a long time and is widely used. The targeting carried out by PERUMDA Air Minum Way Rilau for PPP SPAM water products is focusing on 2 green areas Sukabumi and Sukarame which are not yet reached. There are three classifications carried out by PERUMDA Air Minum Way Rilau regarding PPP SPAM water products, namely positioning based on product, competitors and consumers.